Effect of add-on therapy with leukotriene receptor antagonists and Chungsangboha-tang in patients with asthma: a protocol for a randomized, placebo-controlled, parallel, multicenter trial - Sung-Woo Kang; Hae-Seong Nam; Yang-Chun Park; Jun-Yong Choi; Ki-Tae Kim; Seo-Jung Ha; Kwan-Il Kim; Hee-Jae Jung; Beom-Joon Lee (BMC Complementary Medicine and Therapies)
Abstract Background Asthma is a chronic disease characterized by airway inflammation and obstruction. Treatment aims to control symptoms with minimal medication, using disease-controlling and symptom-relieving drugs. Inhaled steroids and beta2 agonists are common treatments; however, their long-term use can cause side effects. Leukotriene receptor antagonists (LTRAs) are used in combination with inhaled steroids to manage asthma because of their anti-inflammatory and bronchodilatory effects. Combining LTRAs with Chungsangboha-tang (CSBHT), a Korean medicine, may enhance their efficacy. This study aimed to evaluate the potential of CSBHT as an adjunctive therapy for asthma management in a randomized, placebo-controlled, double-blind, multicenter clinical trial. Methods This randomized, placebo-controlled, double-blind, parallel-group, multicenter study aims to evaluate the efficacy and safety of CSBHT as an additional treatment for patients with asthma, particularly for those with LTRAs. Overall, 198 participants will be randomly divided into intervention and control groups, with the former receiving CSBHT thrice daily and the latter receiving a placebo. Follow-ups at weeks 0, 4, and 8 will include outcome measurements, medication dispensation, and adverse reaction monitoring. The primary outcome is the mean change in forced expiratory volume in one-second scores, with secondary outcomes including changes in peak expiratory flow, forced vital capacity, forced expiratory flow 25–75%, fractional exhaled nitric oxide, Asthma Control Test, Asthma Quality of Life Questionnaire, serum IgE, eosinophil count, C-reactive protein, rescue medication usage, and a descriptive analysis of the questionnaire on asthma symptoms in Korean medicine. Safety assessments will be conducted using laboratory tests, vital signs, and monitoring of adverse events. Economic evaluations will be conducted using either cost-minimization analysis or cost-utility analysis. Discussion This trial will evaluate the efficacy, safety, and cost-effectiveness of CSBHT as an add-on therapy to LTRAs to establish its potential as an adjuvant therapy in asthma management. Trial registration This study was registered in the Clinical Research Information Service of Korea (KCT0006005), on March 16, 2021.